Physiological and Biochemical Changes in Vegetable and Field Crops under Drought, Salinity and Weeds Stresses: Control Strategies and Management - Khaled Abdelaal; Moodi Saham Alsubeie; Yaser Hafez; Amero Emeran; Farahat Moghanm; Salah Okasha; Reda Omara; Mohammed A. Basahi; Doaa Bahaa Eldin Darwish; Mohamed F. M. Ibrahim; Ahmed Abou El-Yazied; Emadeldeen Ahmed Rashwan; et al. (Agriculture, 2022)
Weeds are one of the most damaging biotic stresses in crop production, and drought and salinity are considered the most serious abiotic stresses. These factors harmfully affect growth and development in several vegetable and field crops by causing harmful effects on physiological and biochemical characteristics such as water uptake, photosynthesis, relative water content, electrolyte leakage, and antioxidant compounds linked with oxidative stress and the accumulation of reactive oxygen species (ROS). These oxidative stress-related components affect most physiological and biochemical characteristics in plants under natural conditions and environmental stresses, especially weed infestation, salinity, and drought stress. ROS such as superoxide (O2•−), hydrogen peroxide (H2O2), peroxyl radical (ROO•), and singlet oxygen (1O2) are very important molecules produced naturally as by-products of metabolic processes in chloroplasts, mitochondria, peroxisomes, and the apoplast. Under stress conditions such as weed infestation, drought and salinity, the morphological and yield characteristics of stressed plants are negatively affected; however, superoxide (O2•−) and hydrogen peroxide (H2O2) are significantly increased. The negative impact of weeds can be mitigated with integrated controls which include herbicides, allelopathy, and crop rotation as well as the different methods for weed control. The defense system in various crops mainly depends on both enzymatic and nonenzymatic antioxidants. The enzymatic antioxidants include superoxide dismutase, glutathione reductase, and catalase; nonenzymatic antioxidants include ascorbic acid, carotenoids, α-Tocopherols, proline, glutathione, phenolics, and flavonoids. These antioxidant components can scavenge various ROS under several stresses, particularly weeds, drought and salinity. In this review, our objective is to shed light on integrated weeds management and plant tolerance to salinity and drought stresses associated with the ROS and the induction of antioxidant components to increase plant growth and yield in the vegetable and field crops.